FINANCIAL PERFORMANCE OF BANKING INDUSTRY - Ismawati, Kun (Universitas Slamet Riyadi, 2019)
This research aimed to determine the financial performance of banking industry by found out the effect of Capital Adequacy Ratio (CAR), Debt to Equity Ratio (DER), Loan to Deposit Ratio (LDR), Non-Performing Loans (NPLs), on Return on Equity (ROE) in the banking industry on the Indonesia Stock Exchange in the 2011 - 2016 period, either partially dan simultaneous. This is a quantitative case study research, secondary data obtained by documentation method. The population of this study are companies included in the banking industry on the Indonesia Stock Exchange in 2011 to 2016 period. Samples of the research were 41 companies, 28 banks match with the criterias: they issued financial statements periodically during the time of observation. Research data tested by t-test, f-test, test of determination coefficient, and multiple linear regression test. Data analysis results obtained from this research were: 1). CAR has no significant effect on ROE in the banking industry on the Indonesia Stock Exchange in the 2011 - 2016 period,. 2). DER has no significant effect on ROE in the banking industry on the Indonesia Stock Exchange in the 2011 - 2016 period, 3). LDR has no significant effect on ROE in the banking industry on the Indonesia Stock Exchange in the 2011 - 2016 period, 4). NPL have a significant effect on ROE in the banking industry on the Indonesia Stock Exchange in the 2011 - 2016 period, 5). CAR, DER, LDR, and NPL simultaneously have a significant effect on ROE in the banking industry on the Indonesia Stock Exchange in the period 2011 - 2016.